After Effects Guru: Keyframe Assistants. - Robinson, Ian (linkedin.com, 2015)
Explore After Effects tools that help with the animation "between" the animation: Keyframe Assistant, expressions, and third-party assistants like Layer Monkey and Ease and Wizz.